Aerobic biodegradation of palm oil mill effluent (POME) using suitable consortium of microorganisms - Jameel, Ahmad Tariq; Abdul Karim, Mohamed Ismail ([s.n], 2012)
Palm oil mill effluent (POME) constitutes 60% of the wastes generated in typical palm oil mill and its environmental impact has been identified to be harmful to aquatic lives. This project examined the potential of degrading POME with microorganisms that are indigenous to POME. Thus, two microorganisms were isolated from POME using serial dilution (10-1 - 10-10) procedure on solid plates containing Potato Dextrose Agar (PDA), Sabouround Dextrose Agar (SDA) and Malt Extract Agar (MEA), respectively. The two microorganisms (TRQ1 and TRQ2) that consistently appeared on the three media plates were quantified and subjected to extracellular enzymatic activities such as Amylolytic, Gelatinolytic, Cellulolytic and Lipolytic. The results show that TRQ1 and TRQ2 contain Gelatinolytic and Cellulolytic enzymes and this indicates that they are potential cellulase and protease secreting microorganisms which can be utilized for the degradation of cellulosic substrates present in POME particularly for bioremediation, biodegradation and bioconversion purposes. The cheap and wide availability of the material (POME) used as source for the production of these microorganisms indicates their economic importance for industrial applications and environmental sustainability, particularly in converting waste to wealth.